Persistent flocks of diverse motile bacteria in long-term incubations of electron-conducting cable bacteria, Candidatus Electronema aureum - Lustermans, Jamie J. M.; Bjerg, Jesper J.; Burdorf, Laurine D. W.; Nielsen, Lars Peter; Schramm, Andreas; Marshall, Ian P. G. (Frontiers in Microbiology, 2023)
Cable bacteria are centimeters-long filamentous bacteria that oxidize sulfide in anoxic sediment layers and reduce oxygen at the oxic-anoxic interface, connecting these reactions via electron transport. The ubiquitous cable bacteria have a major impact on sediment geochemistry and microbial communities. This includes diverse bacteria swimming around cable bacteria as dense flocks in the anoxic zone, where the cable bacteria act as chemotactic attractant. We hypothesized that flocking only appears when cable bacteria are highly abundant and active. We set out to discern the timing and drivers of flocking over 81 days in an enrichment culture of the freshwater cable bacterium Candidatus Electronema aureum GS by measuring sediment microprofiles of pH, oxygen, and electric potential as a proxy of cable bacteria activity. Cable bacterial relative abundance was quantified by 16S rRNA amplicon sequencing, and microscopy observations to determine presence of flocking. Flocking was always observed at some cable bacteria, irrespective of overall cable bacteria rRNA abundance, activity, or sediment pH. Diverse cell morphologies of flockers were observed, suggesting that flocking is not restricted to a specific, single bacterial associate. This, coupled with their consistent presence supports a common mechanism of interaction, likely interspecies electron transfer via electron shuttles. Flocking appears exclusively linked to the electron conducting activity of the individual cable bacteria.